Cost Efficiency of USAID Markets II Beneficiary Smallholder Rice Farmers in Nigeria’s Kano State - Sanusi Mohammed Sadiq; Invinder Paul Singh; Muhammad Makarfi Ahmad (Indonesian Journal of Agricultural Research, 2021)
The present research attempted to address cost inefficiency of USAID MARKETS II smallholder farmers in Nigeria’s Kano State using farm survey data obtained from 189 farmers through a multi-stage sampling technique. The farm survey data were elicited viz. well-structured questionnaire coupled with interview schedule during the 2018 cropping season. The collected data were analyzed using both descriptive and inferential statistics- stochastic cost frontier function. The empirical evidence showed that none of the technical unit was cost efficient and this owed majorly to extension gap given its interwoven link with risk inducing factors. Besides, only 57.7%, marginally above half of the sampled technical units were fairly cost efficient i.e. close to the optimum minimum cost preferred for the production process. On the average, a technical unit wasted 14.7% of its actual incurred cost which translates to N1100 ($3.7) relative to the best practiced farmers facing the same technology and producing the same output. Therefore, since the farmers still have the room to eliminate the extra cost incurred, the study advice the program to explore further the advisory services offered to the farmers, thus addressing the extension gap that inhibited the farmers’ cost efficiency. The sustainability of the project in the near future in the absence of the advisory services especially farmer-2-farmer extension services if not explored is unlikely.